"Efectividad de un Programa Educativo y Nivel de Conocimiento Sobre Caries Dental en Madres de Preescolares" - Quiliche Mosqueira, Nadia (2015)
The present quantitative investigation is a type experimental Pre, realized in the district El Porvenir -Gran Chimú, with the objective to determine the effectiveness of the Educational Program: " DIENTES SANITOS " at the level of knowledge on Dental Caries in mothers of pre-school of Educational Initial Institution 1562 " Bello Horizonte ", during April - May, 2015. The sample universe was conformated to 40 mothers that they complied with the criteria of mentioned in the investigation. For the compilation of information the instrument was in use: Test to measure the level of Knowledge in Mothers on Dental decay (TMNCMSCD), being the obtained information processed and analyzed by Square Chi of MCNECMAR statistical test. The results are presented in tables of simple and double entry. After the analysis it came near to the following conclusions Before the application of the Educational Program, 92.5 mothers' per cent of pre-school obtained a level of Regular knowledge. After the application of the Educational Program, 90 mothers' per cent of pre-school obtained a level of Good knowledge. The educational program was effective in increasing the level of knowledge in mothers of kindergartens on Dental Caries (P = 0.0000). Key words: Maternal knowledge, educational program and Dental Caries.